Techno-economic analysis of an integrated electrocoagulation-membrane system in treatment of palm oil mill effluent - Saad, M.S. (Elsevier B.V., 2022)
Palm oil mill effluent (POME) is an oily wastewater generated by palm oil processing mills. Most palm oil factories and refineries have their own treatment system such as anaerobic digestion system and electrocoagulation (EC). In this study, a new method, integrated electrocoagulation (EC)-membrane system is introduced to treat the POME. The treatment efficiency and economic feasibility of the developed integrated EC-membrane is also evaluated by comparing with EC standalone system. This study highlights that the removal of POME by EC has increased with extended time and increasing voltage. Besides, the integrated EC-membrane shows better removal efficiency compared to the EC system. For model development, both standard least squares model for EC and integrated membrane-EC systems created by using JMP software showed a good fit and able to be used for further efficiency calculation. The economic analysis result shows that integrated EC-membrane method has a higher capital cost with lower in the operating cost per year than EC method. 75 color removal efficiency is achievable by integrated EC-membrane system at voltage 1 V and 2 V in which EC method requires voltage of 4 V and higher. Notably, the total cost of integrated EC-membrane system at the first year of implementation is lower than the EC system and in 15 years period has a 21.24 lesser cost compared to EC system. Â© 2022 The Author(s)